2020
DOI: 10.1074/jbc.ra119.012419
|View full text |Cite
|
Sign up to set email alerts
|

Heparin inhibits proinflammatory and promotes anti-inflammatory macrophage polarization under hyperglycemic stress

Abstract: Monocytes are rapidly recruited to sites of diabetic complications and differentiate into macrophages. Previously, we showed that rat kidney mesangial cells dividing during hyperglycemic stress abnormally synthesize hyaluronan (HA) in intracellular compartments. This initiates a stress response, resulting in an extracellular HA matrix after division that recruits inflammatory cells. Cell–cell communication among macrophages that are recruited into the glomeruli and the damaged rat mesangial cells leads to diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 37 publications
2
19
0
1
Order By: Relevance
“…[ 61 ] Moreover, when exposed to macrophages, they showed that heparin locally sequesters the macrophage produced growth factors. While potential effects of heparin by itself on macrophage polarization have been suggested, [ 62 ] no clear effect of heparin on macrophage polarization was observed as the bare and heparin group both showed a trend toward more M1 (iNOS+) macrophages and lower M2 (Arg+) macrophages, which is in correspondence to our previous in vitro data on this materials. [ 23 ] This may explain why we did not observe hyperplasia in the IL‐4/hep dual‐functionalized group, as the growth factor and cytokine release profile would be altered by the IL‐4‐induced macrophage polarization, although this warrants further investigation.…”
Section: Discussionsupporting
confidence: 89%
“…[ 61 ] Moreover, when exposed to macrophages, they showed that heparin locally sequesters the macrophage produced growth factors. While potential effects of heparin by itself on macrophage polarization have been suggested, [ 62 ] no clear effect of heparin on macrophage polarization was observed as the bare and heparin group both showed a trend toward more M1 (iNOS+) macrophages and lower M2 (Arg+) macrophages, which is in correspondence to our previous in vitro data on this materials. [ 23 ] This may explain why we did not observe hyperplasia in the IL‐4/hep dual‐functionalized group, as the growth factor and cytokine release profile would be altered by the IL‐4‐induced macrophage polarization, although this warrants further investigation.…”
Section: Discussionsupporting
confidence: 89%
“…The results suggest that the intensive nursing of hyperglycemia optimization management can effectively improve the degree of nerve defect and the ability of daily living in patients with cerebral hemorrhage after operation. This is due to the optimal management of hyperglycemia intensive nursing inter-vention mode of patients with better blood glucose control can avoid hyperglycemia damage to neurons [27][28][29]. Hyperglycemia can increase the anaerobic metabolism of brain tissue, destroy mitochondria, produce a large number of free radicals, and increase the Ca2 + influx of nerve cells [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hyperglycemia seems to be involved in the “trained immunity” (the nonspecific, immunological memory of past insults) through epigenetic modifications that sustain inflammation and transcriptional activation of genes involved in atherosclerosis [ 101 , 104 ]. Interestingly, on the other hand, heparin inhibits the proinflammatory polarization of macrophages in hyperglycemic conditions and promotes an anti-inflammatory phenotype of these cells [ 105 ].…”
Section: Chronic Inflammation In Obesity and Type 2 Diabetesmentioning
confidence: 99%